Methods for U-series dating of CaCO 3 crusts associated with Palaeolithic cave art and application to Iberian sites - Hoffmann, Dirk L. (2018)
U-series dating is a precise and accurate geochronological tool which is widely applied to date secondary CaCO3 formation, for example in speleothem based palaeoclimate research. It can also be employed to provide chronological constraints for archaeological sites which have a stratigraphic relationship with speleothem formations.We present in detail our methods to conduct precise and accurate U-Th dating of calcite crusts that formed on top of cave paintings. Our protocols allow the application of U-series measurements on small, thin calcite crusts covering cave art, which can be found in many sites, while taking care not to harm the art underneath. The method provides minimum ages for the covered art and, where possible, also maximum ages by dating the flowstone layer the art is painted on. We present dating results for crusts from two locality types in Spain, a typical cave environment (La Pasiega) and a more open, rock shelter type cave (Fuente del Trucho).